Hsa_circ_0004370 promotes esophageal cancer progression through miR-1294/LASP1 pathway. Issue 5 (14th May 2019) - Zhang, Zhenyang; Lin, Wenwei; Gao, Lei; Chen, Keqing; Yang, Chuangcai; Zhuang, Linwei; Peng, Shuai; Kang, Mingqiang; Lin, Jiangbo
Abstract : Circular RNAs (circRNAs) formed by back-splicing play multiple roles in the occurrence and development of cancer. Here, we found that hsa_circ_0004370 was up-regulated in both esophageal cancer (EC) tissues and cell lines. Loss function of hsa_circ_0004370 by si-RNA significantly suppressed proliferation and invasion and promoted apoptosis in both EC cell lines. The sponging of miR-1294 by hsa_circ_0004370 was bioinformatically predicted and subsequently verified by luciferase reporter assay and RNA immunoprecipitation assay. Further, hsa_circ_0004370 involved in the up-regulation of LASP1 by sponging miR-1294. Besides, the inhibition of the down-regulated hsa_circ_0004370 on cell malignant behaviors was rescued by miR-1294 inhibitor. Finally, this rescue effect was abrogated by suppressing the expression of LASP1. The results present here suggest that hsa_circ_0004370 functions as an oncogene on cell proliferation, apoptosis, and invasion via miR-1294/LASP1 axis.